Intractable cough and abnormal pulmonary function in benign recurrent intrahepatic cholestasis - Chatila, R. (1996)
Benign recurrent intrahepatic cholestasis (BRIC) is a syndrome characterized by recurrent episodes of cholestasis with associated pruritus. The intensity and duration of cholestatic episodes, and the length of the intervening periods, vary. unpredictably. We report the case of a patient with BRIC who was incapacitated by a severe intractable cough that accompanied marked pruritus during her second cholestatic episode. No cause for the cough was found, and it resolved spontaneously with amelioration of mild restrictive abnormalities of pulmonary function as the cholestasis subsided. Although cough has not been recognized as a complication of cholestasis, we postulate that it may occur either (i) as a result of direct stimulation of sensory nerves by circulating humoral substances related to the cholestasis that act either peripherally in the airways or centrally, or (ii) through stimulation of the vagus nerve in the liver, leading to cough that is mediated either centrally or by reflex.